Endoscopic Prediction of Crohn's Disease Postoperative Recurrence. Issue 5 (7th July 2021) - De Cruz, Peter; Hamilton, Amy L; Burrell, Kathryn J; Gorelik, Alexandra; Liew, Danny; Kamm, Michael A
Abstract: Background: The presence and severity of endoscopic recurrence after Crohn's disease intestinal resection predicts subsequent disease course. The Rutgeerts postoperative endoscopic recurrence score is unvalidated but has proven prognostically useful in many clinical studies. This study aimed to investigate the association between specific early endoscopic findings and subsequent disease course. Methods: In the setting of a randomized controlled trial (the POCER study), 85 patients underwent colonoscopy at 6 and 18 months after intestinal resection. Patients received 3 months of metronidazole, and high-risk patients received a thiopurine (or adalimumab if they were thiopurine intolerant). For endoscopic recurrence (Rutgeerts score ≥i2) at 6 months, patients stepped up to a thiopurine, fortnightly adalimumab with thiopurine, or weekly adalimumab. Central readers confirmed Rutgeerts, Simple Endoscopic Score for Crohn's Disease, Crohn's Disease Endoscopic Index of Severity scores, and 5 newly tested endoscopic parameters: anastomotic ulcer depth (superficial vs deep), number of ulcers (0, ≤2, >2), ulcer size (1-5 mm, ≥6 mm), circumferential extent of ulceration (<25%, ≥25%), and the presence or absence of stenosis. The POCER index, based on the 6-month postoperative findings, was then developed in relation to predicting the endoscopic outcome at 18 months. Results: Of the 5 parameters, the combination of ulcer depth and circumference at the anastomosis at 6 months was associated with endoscopic recurrence at 18 months (odds ratio [OR], 1.6; 95% confidence interval [CI], 1.03-2.50; P  = 0.035) with an area under the receiver operating characteristic curve of 0.62 (95% CI, 0.5-0.75). The combination of these 2 parameters formed the basis of the POCER index (range, 0-4 with 0 denoting no ulcers and 4 denoting deep ulceration with >25% circumferential involvement). The new index had a strong correlation with the Rutgeerts score measured at the same time points: Spearmans' r  = .80 at 6 months and r  = .77 at 18 months ( P  < 0.001 at both time points). A POCER index of ≥2 and a Rutgeerts score of ≥i2 both had a sensitivity of 0.41 for recurrence; however, the POCER index had a higher specificity (0.8 and 0.67, respectively). The POCER index at 6 months was associated with endoscopic recurrence at 18 months (OR, 1.5; 95% CI, 1.2-2.0; P  = 0.002; area under the receiver operating characteristic curve of 0.70; 95% CI, 0.57-0.82), but the Rutgeerts score was not (OR, 1.2; 95% CI, 0.8-1.8; P  = 0.402). Conclusions: The POCER postoperative index comprises 2 key endoscopic factors related to the anastomosis that are associated with subsequent disease progression. A higher score, comprising the adverse prognostic factors of deep or circumferentially extensive anastomotic ulceration, may help identify patients who require more intensive therapy.